Potential of Remote Patient Monitoring in Perioperative Care: A Narrative Review - Leonard Simeth; P. J. Devereaux; Michael McGillion; Jochen D. Muehlschlegel; Jakob Wollborn (Anesthesiology, 2026)
Remote patient monitoring is moving closer to routine implementation and has the potential to become an important component of perioperative care: with wearables being able to monitor increasingly more biosignals with acceptable accuracy, the technological foundation is being laid for perioperative management that extends beyond hospital walls. Preoperatively, remote patient monitoring data are being explored for risk prediction and prehabilitation with the goal of improving risk stratification and better preparing patients for surgery. Postoperatively, continuous monitoring on wards and after discharge can enable earlier detection and intervention in case of deterioration, with the potential to improve patient safety and facilitate early discharge. Large clinical trials are ongoing and will provide further evidence on outcomes. With increasing emphasis on perioperative care, a new subspecialty of physicians may emerge who will act as perioperative care navigators, coordinating artificial intelligence–supported clinical decision-making. This narrative review synthesizes infrastructure, devices, and implementation across the surgical continuum.